29=43+x

Simple and best practice solution for 29=43+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 29=43+x equation:



29=43+x
We move all terms to the left:
29-(43+x)=0
We add all the numbers together, and all the variables
-(x+43)+29=0
We get rid of parentheses
-x-43+29=0
We add all the numbers together, and all the variables
-1x-14=0
We move all terms containing x to the left, all other terms to the right
-x=14
x=14/-1
x=-14

See similar equations:

| p+7(-6p-8)=-179 | | 6+6z=30 | | 36=x-5 | | 8(b-9)^3-20=980 | | 8f+f/2=17 | | 1+3x=8+7x-3x | | 108=7(7-8r)-3r | | 9v^2+36v-108=0 | | 3=11-v÷9 | | 9-3(t-5)=12-6t | | 11-v÷9=3 | | 6+4(2-5m)=-126 | | 3x5=2 | | 72-28=10x | | 4(8p+8)=192 | | 5/13=t-16/13 | | 5(-6x-5)=-2-7x | | 3(-5x+4)+5x-1=3(−5x+4)+5x−1=-39 | | 3k^2-3k-4=7 | | 14b+3b-9b+b-8b=13 | | -11(q+5)=-90-4q | | 7x+4x-8x-2x=20 | | 8-5x+3x=25 | | 13x-12x+2x-2x=11 | | 15=1.5×+1y | | 8b+3b-7b+b-4b=18 | | (6p-2)/7=(5p+7)/8 | | 45x+109=437.50 | | 2a+3a-4a=17 | | 2x+5=3x+93 | | 3x-6+2x+6=180 | | 8p-6p-1=11 |

Equations solver categories